Therapeutic efficacy test in malaria falciparum in Antioquia, Colombia (2006)
ABSTRACT: Objective: Evaluate the frequency of failure of eight treatments for non-complicated malaria caused by Plasmodium falciparum in patients from Turbo (Urabá region), El Bagre and Zaragoza (Bajo Cauca region), applying the 1998 protocol of the World Health Organization (WHO). Monotherapies using chloroquine (CQ), amodiaquine (AQ), mefloquine (MQ) and sulphadoxine-pyrimethamine (SP), and combinations using chloroquine-sulphadoxine-pyrimethamine (CQ-SP), amodiaquine-sulphadoxine-pyrimethamine (AQ-SP), mefloquine-sulphadoxine-pyrimethamine (MQ-SP) and artesunate-sulphadoxine-pyrimethamine (AS-SP), were examined. Methodology: A balanced experimental design with eight groups. Samples were selected based on statistical and epidemiological criteria. Patients were followed for 21 to 28 days, including seven or eight parasitological and clinical evaluations, with an active search for defaulting patients. A non-blinded evaluation of the antimalarial treatment response (early failure, late failure, adequate response) was performed. Results: Initially, the loss of patients to follow-up was higher than 40%, but the immediate active search for the cases and the monetary help for transportation expenses of patients, reduced the loss to 6%. The treatment failure was: CQ 82%, AQ 30%, MQ 4%, SP 24%, CQ-SP 17%, AQ-SP 2%, MQ-S-P 0%, AS-SP 3%. Conclusion: The characteristics of an optimal epidemiological monitoring system of antimalarial treatment response in Colombia are discussed. It is proposed to focus this on early failure detection, by applying a screening test every two to three years, based on a seven to 14-day follow-up. Clinical and parasitological assessment would be carried out by a general physician and a field microscopist from the local hospital, with active measures to search for defaulter patients at follow-up.